THE INTEGRATION OF PRACTICAL AND THEORETICAL KNOWLEDGE IN THE DEVELOPMENT OF A SINGER'S MASTERY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The article discusses the formation of a singer's performance skills, highlighting the harmony between practical and theoretical knowledge in lessons and practical exercises. It also addresses emerging challenges and proposes effective solutions based on the outcomes of these practical activities.